Web based home automation system using arduino - Chikahe, Allen (Midlands State University, 2019)
The aim of home automation is to control home devices from a central control point. In this paper, I present the design and implementation of a low cost but yet flexible and secure internet based home automation system. Nowadays, Internet has spread worldwide and most of the internet connections use Ethernet as media for data transfer. In industries or in home appliances, most of the time we need to monitor and control different parameters using microcontrollers. The popularity of home automation has been increasing greatly in recent years due to much higher affordability and simplicity through Smartphone and tablet connectivity. The concept of the "Internet of Things" has tied in closely with the popularization of home automation. Ethernet provides inexpensive, relatively high speed network access to individual users and low delay that can support many applications. This implementation is an attempt to connect an embedded device to an Ethernet. Using Ethernet based system we can control various home appliances from anywhere across the world. The existing system which uses the GSM,GPRS, Bluetooth, Zigbee Infrared and RFID technology which are having its own limitations notably of delays in signal propagations and limited distances associated with GSM communication ,Bluetooth and Infrared communication respectively.